Fabrication of polyethersulfone membrane by polyethyleneglycol coated cobalt-doped iron oxide for copper (II) removal - Chan, Kian Hwa (2015)
Today, research and development of membrane technology are focused towards the improvement of properties and performances through membrane modification by using nanoparticles. In this research, hydrophobic cobalt-iron oxide nanoparticles were coated with polyethylene glycol (PEG) molecular weight MW-600 to prevent the agglomeration of nanoparticles and to improve its dispersion before adding into the dope solution containing 20 wt% polyethersulfone (PES) in dimethylformamide (DMF). The nanomodified membranes were characterized in terms of flux permeation (Q), wetting ability and solute separation. The prepared modified ultrafiltration membranes were then subjected to the separation of copper (II) ions and the separation efficiency of the nanoparticles modified membrane were found to improve significantly. This may be due to synergistic interaction between two additives that improved the structure as well as the performance of PES ultrafiltration membrane in terms of copper (II) rejection. The incorporation of 6% nanoparticles in the membranes had improved the copper (II) rejection from 10% to >90% with initial concentration of copper (II) at 20 ppm in cross flow filtration cell at pH 7. The membrane modified with nanoparticles also exhibited good regeneration ability and could be reused for more than five times without significantly drop in performances. In conclusion, incorporating of cobalt iron oxide nanoparticles coated with PEG can improve the copper (II) rejection of modified ultrafiltration membrane.